The role of the state in development processes - Auroi, Claude (London ; Portland, Ore. : F. Cass, 1992)
Gives an overview of various state interventions in Africa, the Arab world, Asia, Europe and Latin America.
"Published in collaboration with the European Association of Development Research and Training Institutes (EADI), Geneva."
First Published in 1992. Routledge is an imprint of Taylor & Francis, an informa company.
Includes bibliographical references.
oif 05/08/16
Loan
Keywords: Economic development; State; Democracy; Industrial policy; Political participation